2022
DOI: 10.1016/j.brs.2022.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial focused ultrasound induces sustained synaptic plasticity in rat hippocampus

Abstract: Transcranial focused ultrasound (tFUS) neuromodulation provides a promising emerging non-invasive therapy for the treatment of neurological disorders. Many studies have demonstrated the ability of tFUS to elicit transient changes in neural responses. However, the ability of tFUS to induce sustained changes need to be carefully examined. In this study, we use the long-term potentiation/long term depression (LTP/LTD) model in the rat hippocampus, the medial perforant path (mPP) to dentate gyrus (DG) pathway, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…The 100 Hz condition was significantly higher than all other conditions ( p < 1e-7), while the 50 Hz condition was significantly lower than all except the 10 Hz condition ( p < 1e-5). This interestingly appears to align with the previous hippocampus result of 50Hz causing LTD (Niu et al, 2022b)Here, we observe that in response to 50 Hz ultrasound stimulation, on average, the network undergoes a decrease in correlation. In about half of the cases these correlation changes appear to last for the remainder of the session time, although in others the change only lasts for 10-20 minutes much like the firing rate changes (Figure 4A-C).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The 100 Hz condition was significantly higher than all other conditions ( p < 1e-7), while the 50 Hz condition was significantly lower than all except the 10 Hz condition ( p < 1e-5). This interestingly appears to align with the previous hippocampus result of 50Hz causing LTD (Niu et al, 2022b)Here, we observe that in response to 50 Hz ultrasound stimulation, on average, the network undergoes a decrease in correlation. In about half of the cases these correlation changes appear to last for the remainder of the session time, although in others the change only lasts for 10-20 minutes much like the firing rate changes (Figure 4A-C).…”
Section: Resultssupporting
confidence: 89%
“…Following our group’s previous work in the hippocampus examining the ability of ultrasound to induce plasticity changes(Niu et al, 2022b), we next examined whether ultrasound was capable of causing correlation changes in S1. Examining the changes in correlation induced between every pair of neurons in a session, it was observed that every frequency resulted in a significant average correlation change besides 10 Hz ( p < 1e-4) (Figure 4G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological formation of these neurons within the hippocampus leads to the further subfield classification of pyramidal cells in what is known as Cornu Ammonus (CA), divided into CA1, CA2, and CA3 [ 49 , 50 ]. These regions serve an important role in localizing KCNQ channel function in synaptic plasticity [ 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Within synaptic plasticity, two major models involved in the application of neural plasticity are long-term potentiation (LTP) and long-term depression (LTD) [ 59 ].…”
Section: Modulation Of Synaptic Plasticity By Kcnq Channelsmentioning
confidence: 99%
“…These regions serve an important role in localizing KCNQ channel function in synaptic plasticity [ 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Within synaptic plasticity, two major models involved in the application of neural plasticity are long-term potentiation (LTP) and long-term depression (LTD) [ 59 ]. These models are activity-dependent, and the literature establishes their role in namesake enhancement or reduction in synaptic efficiency.…”
Section: Modulation Of Synaptic Plasticity By Kcnq Channelsmentioning
confidence: 99%